2020
DOI: 10.1007/s00294-020-01130-7
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in populations of enterohaemorrhagic Escherichia coli undergoing d-serine adaptation

Abstract: Phenotypic and genetic heterogeneities are conserved features of prokaryotic populations. During periods of stress, this programmed diversity increases the likelihood that variants within the population will survive the adverse conditions, allowing for proliferation. Phenotypic heterogeneity can have a mutational or indeed a non-mutational basis as observed in bet-hedging strategies adopted by antibiotic-tolerant persister cells. Genetic variants can arise by phase variation (slip-strand mispairing, promoter i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Draft genome sequencing indicated that there were differences in plasmid content between the two groups of strains analyzed. Understanding the biological reasons that systemic and cecal E. coli are different is difficult without knowing the exact pressures that these groups of E. coli are subject to (Reisner et al, 2006;Brzuszkiewicz et al, 2009;Coombes, 2009;Azevedo et al, 2016;O'Boyle and Roe, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Draft genome sequencing indicated that there were differences in plasmid content between the two groups of strains analyzed. Understanding the biological reasons that systemic and cecal E. coli are different is difficult without knowing the exact pressures that these groups of E. coli are subject to (Reisner et al, 2006;Brzuszkiewicz et al, 2009;Coombes, 2009;Azevedo et al, 2016;O'Boyle and Roe, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been reported more recently. 145,146 The mechanism remains elusive; however, D-Ser may be involved in cell growth and/or incorporation into peptidoglycan, where alterations in cell wall structure may subsequently alter virulence. Found in chemosensory cells within the upper respiratory epithelium when stimulated, sweet taste receptor (T1R) inhibits the release of AMPs by neighboring cells.…”
Section: Prokaryote Production Of D-aasmentioning
confidence: 99%